A lite too bright - Miller, Tim, 1972- (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
After losing his college scholarship, Arthur discovers a journal written by his deceased grandfather and decides to follow the train route to the destination mentioned in the last sentence of the journal.